Assessing the effect of social commerce in shaping fashion purchase intent among working professionals - Niyaz Panakaje; Madhura K.; S. M. Riha Parvin; Jeevan Raj; Nushruth S; Shakira Irfana; Rovina Sharon Soans (Innovative Marketing, 2025)
Type of the article: Research Article AbstractRetailers are leveraging social commerce by integrating advanced social media features to drive customer engagement and create superior value. Thus, a present study is an attempt to analyze the impact of perceived ease of use, user engagement and technological factors on social commerce usage and to assess its contribution towards the purchase intention of the working professionals. 380 working women (from organized sectors including education, industry, health, government, banking, and IT) were targeted from Bengaluru city of India by adopting the snowball sampling method which was further analyzed using independent sample t-test, regression analysis, and Structural Equation Modelling. The results of the study show the effects of perceived ease of use (β = .434), user engagement (β = .517), and technological factors (β = .662) on social commerce usage (SCU) are studied, which mediates purchase intention (β = .689). These results indicate that SCU is one of the main factors affecting purchase intention (β = .751). This also show that there is significant influence of perceived ease of use, user engagement, and technological factors on social commerce usage that has ultimately led to their purchase intention among working professionals. Based on these findings, it is crucial to perfect social commerce strategies in order to improve consumer’s engagement and encourage purchase behavior.